2021
DOI: 10.1029/2020jc016713
|View full text |Cite
|
Sign up to set email alerts
|

Slope‐Intensified Storm‐Induced Near‐Inertial Oscillations in the South China Sea

Abstract: Near-inertial oscillations (NIOs) are commonly observed in the ocean as responses to a sudden change of the wind direction during passages of either cold fronts or tropical cyclones (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Significant peaks at frequency f (about 0.705 cpd in Figure 11A) showed up indicating that strong NIWs were triggered by the typhoon in this area. Similar stormgenerated near-inertial oscillations have been reported by many studies (Hormann et al, 2014;Zhang et al, 2014;Alford et al, 2016;Li et al, 2021a;Zhang et al, 2021).…”
Section: Buoyancy Frequency and Niwssupporting
confidence: 86%
See 2 more Smart Citations
“…Significant peaks at frequency f (about 0.705 cpd in Figure 11A) showed up indicating that strong NIWs were triggered by the typhoon in this area. Similar stormgenerated near-inertial oscillations have been reported by many studies (Hormann et al, 2014;Zhang et al, 2014;Alford et al, 2016;Li et al, 2021a;Zhang et al, 2021).…”
Section: Buoyancy Frequency and Niwssupporting
confidence: 86%
“…At the surface layer, the advection terms showed significant wave signals along the shelf break off southeastern Hainan Island on July 15 (Figure 14) and the wave signals became much stronger on July 18 and 19 with the passage of the typhoon. This kind of typhoon-induced wave has been observed frequently in the northern SCS (Sun et al, 2015;Zheng et al, 2015;Li et al, 2021a;Li et al, 2022). Li et al (2021a) found that the stormgenerated near-inertial oscillations exhibit a slope-intensified feature on the northern slope of the SCS, regardless of typhoon trajectory and intensity.…”
Section: Temperature Transport Processmentioning
confidence: 80%
See 1 more Smart Citation
“…The South China Sea (SCS), a marginal sea located in the northwestern Pacific Ocean, is frequently influenced by locally and western Pacific Ocean generated tropical cyclones [21]. Basic characteristics of NIWs induced by tropical cyclones in the SCS have been analyzed based on in situ observations [19,20,[22][23][24][25][26][27][28] and numerical modelling [29][30][31][32]. NIWs in the SCS are frequently modified by background relative vorticity [23,28,33,34], nonlinear wave-wave interactions [33,35,36], and internal tides [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Basic characteristics of NIWs induced by tropical cyclones in the SCS have been analyzed based on in situ observations [19,20,[22][23][24][25][26][27][28] and numerical modelling [29][30][31][32]. NIWs in the SCS are frequently modified by background relative vorticity [23,28,33,34], nonlinear wave-wave interactions [33,35,36], and internal tides [37,38].…”
Section: Introductionmentioning
confidence: 99%